Computerized Accounting with Peachetree 8.0 - Mazza, Jim and Gary Chavez (Montreal EMCParadigm, 2002)
Computerized Accounting with Peachetree 8.0 teachers all the key accounting software skills supported in Peachtree Complete Accounting, Version 8.0. In addition, it cover the accounting concepts associated with each chapter in substential detail for a software textbook. The is presented in a clear and concise manner, with a step-by-step approach to introduce new functions.
Keywords: Economics